A laboratory scale bioremediation of Tapis crude oil contaminated soil by bioaugmentation of acinetobacter baumannii T30C - Chang, L.K; Ibrahim, D.; Omar, I.C. (Academic Journals, 2011)
Microbial degradation of Tapis crude oil contaminated soil by Acinetobacter baumannii T30C was conducted to evaluate the efficiency of the selected potential hydrocarbon degrader in stimulating bioremediation of crude oil-contaminated soil with different treatment units in microcosms with 2.5 kg soil. Previously, A. baumannii T30C was isolated from a Tapis crude oil-contaminated soil of oil refinery plant, Terengganu, Malaysia. The reduction of residual hydrocarbons in the soil was observed for a period of about 35 days. The study showed that amendment of nutrients was needed for stimulating the growth of A. baumannii T30C and indigenous microorganism in assisting the degradation of residual hydrocarbons in the soil.